(7,8-Dimethyl-2-oxo-2H-chromen-4-yl)methyl piperidine-1-carbodithioate - A. J. Ravi; K. Mahesh Kumar; H. C. Devarajegowda (IUCrData, 2016)
In the title compound, C18H21NO2S2, the 2H-chromene ring systems is nearly planar, with a maximum deviation of 0.023 (2) Å. The coumarin unit makes a dihedral angle of 60.54 (8)° with the piperidine ring, which adopts a chair conformation. The carbodithioate group is present in a synperiplanar conformation with respect to the piperidine ring, as indicated by the torsion angle of −4.7 (2)°. A short intramolecular C—H...S conatct generates an S(5) ring. No directional interactions beyond van der Waals contacts could be identified in the crystal.